Burnout among midwives and attitudes toward midwifery: a cross-sectional study from Baden-Württemberg, Germany - Paul, Nicolas; Limprecht-Heusner, Marcus; Eichenauer, Jutta; Scheichenbauer, Christel; Bärnighausen, Till; Kohler, Stefan (European journal of midwifery, 2022)
Introduction: Midwifery services are a cornerstone of maternal care, but the mental health of midwives is at risk in many work settings. The aim of this study was to assess burnout and attitudes toward midwifery among midwives in Baden-Württemberg, Germany.